Survival features, prognostic factors, and determinants of diagnosis and treatment among Iranian patients with pancreatic cancer, a prospective study. - Mahdi Sheikh; Sahar Masoudi; Razieh Bakhshandeh; Alireza Moayyedkazemi; Farhad Zamani; Sepideh Nikfam; Masoumeh Mansouri; Neda Ghamarzad Shishavan; Saman Nikeghbalian; Paul Brennan; Reza Malekzadeh; Akram Pourshams (PLoS ONE)
Objectives Investigating the survival features, and determinants of treatment and stage at presentation in Iran. Methods 461 patients with pancreatic ductal adenocarcinoma (PC) were prospectively enrolled from Shariati hospital, Tehran, Iran, between 2011-2018. All patients underwent endoscopic ultrasonography, computed tomography scanning, and physical examination. Validated questionnaire was completed for the participants and all were actively followed on monthly basis. Results Median survival time was 6.5 months, and 1-, and 5-year survival rates were 26.2%, and 1.5%. Patients who were older (p<0.001), illiterate (p = 0.004), unmarried (p = 0.003), rural inhabitant (p = 0.013), opium user (p = 0.039), and had lower body mass index (BMI) (p = 0.002) had lower overall survival. Tumors located in the head of pancreas were more commonly diagnosed at lower stages (p<0.001). Only 10.4% of patients underwent surgery who were more commonly educated (p<0.001), married (p = 0.005), had a tumor located in the head of pancreas (p = 0.016), and were diagnosed at lower stages (p<0.001). After adjustment for potential confounders and risk factors, rural inhabitance (HR: 1.33 (95% CI: 1.01-1.74)), having more symptoms (HR for each increasing symptom: 1.06 (1.02-1.11)), using opium (HR: 1.51 (1.04-2.20)), having a tumor located in the body of pancreas (HR: 1.33 (1.02-1.75)), and having an advanced tumor stage (HR: 2.07 (1.34-3.19)) remained significantly associated with increased risk of mortality. After the adjusting for potential confounders, we did not find significant relationships between smoking, alcohol intake, and BMI with the risk of death among patients with pancreatic cancer. Conclusions Iranian patients with PC have very poor long-term survival. Besides tumor's stage and location, socioeconomic disparities could affect the probabilities of receiving treatment and/or survival in these patients. Opium use is an independent risk factor for mortality among PC patients in Iran.